The social context of violence in the novel Rabies by Borislav Pekić - Zdravković, Sara; Pejković, Kristina (Sociološki pregled, 2025)
The subject of the paper is the motif of violence as a social phenomenon in the novel Rabies by Borislav Pekić. The paper examines the degree of literary mediation of violence as a social issue, addressing the dilemma about its inherence, as well as situations in which it seems unavoidable or is even met with approval. The role of the relationship between an individual and a group in manifesting violence is also analyzed. In general, social sciences and humanities offer exclusive perspectives on human nature by adopting either a Rousseauesque or Hobbesian approach. The sociological analysis in this paper aims to elucidate one-sided views on human nature and the question of civilized society, by referring to the ambivalent status of violence in emergency situations and certain social contexts. From a literary-theoretical perspective, the airport in quarantine is analyzed as a metaphor for society in crisis, with Heathrow witnessing power struggles, political disagreements, as well as ethnic and personal conflicts. It is shown that through the analysis evil as a phenomenon, using recurring motifs of genetic engineering and “the escaped virus”, Rabies shows tendencies of social commentary that align with science fiction discourse. The aim of this paper is to explore the complex dynamics between individuals, emergency situations and authority, which are conducive to relativizing the meaning of violence, and the factors contributing to its acceptance, of which Pekić s novel warns.